Soil-site suitability evaluation for maize crop in Aravalli landscape of Banswara district, Rajasthan - Meena, R.H.; Giri, J.D.; Choudhary, S.R.; Shyampura, R.L. (Annals of Agricultural Research, 2014)
The major soils of Banswara district in Rajasthan were evaluated for their suitability for maize cultivation using limitation method regarding number and intensity of limitations. The study suggests that maize is highly suitable in soils of Pedon P9 but moderately suitable in soils of Pedon P4, P7 and Pedon P8. Whereas soils of Pedon P1, P2 and Pedon P6 are marginally suitable and soils of pedon P3 and Pedon P5 are not suitable for maize cultivation. Soil depth, drainage, erosion and organic carbon are the major limitations for crop growth in the most of soils of Aravalli landscape. The suitability classes can be improved if the correctable limitations (soil fertility characteristics) are altered through soil amelioration measures.